1998
DOI: 10.1002/(sici)1521-4044(199808)49:8<404::aid-apol404>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the copolymerization of styrene and maleic anhydride prepared in carbon tetrachloride and in N,N-dimethylformamide

Abstract: Styrene (ST or 1) and maleic anhydride (MA or 0) were copolymerized in carbon tetrachloride (CCl 4 ) and in N,N-dimethylformamide (DMF) with a wide range of MA mole fraction in the feed (f 0 = 0.01 to 0.90) at 50 8C. The DEPT 13 C NMR subspectra of methylene carbon of ST(1) units were used to determine the ST(1) centered triad mole fractions (F 010 , F (011 + 110) , F 111 ). Non-linear least squares (NLLS) curve fitting was used to fit the theoretical equations of the five copolymerization models, namely, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Styrene and maleic anhydride are known to produce alternating copolymers [31][32][33] that have been used in a variety of applications. 32 Maeda and co-workers used low molecular weight PSMA copolymers (<6 kDa) clinically to deliver the antitumor protein neocarzinostatin (NCS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Styrene and maleic anhydride are known to produce alternating copolymers [31][32][33] that have been used in a variety of applications. 32 Maeda and co-workers used low molecular weight PSMA copolymers (<6 kDa) clinically to deliver the antitumor protein neocarzinostatin (NCS).…”
Section: Introductionmentioning
confidence: 99%
“…Styrene and maleic anhydride are known to produce alternating copolymers that have been used in a variety of applications . Maeda and co-workers used low molecular weight PSMA copolymers (<6 kDa) clinically to deliver the antitumor protein neocarzinostatin (NCS). , The polymer−protein conjugate, known as SMANCS, is formed using “partial half-esters” of SMA, in which 70% of the maleic anhydride groups were opened using butanol. , SMANCS significantly improved the pharmacological properties of NCS by increasing both its circulatory half-life and its lipid solubility, and it has been clinically effective in treating liver cancer. , The SMANCS conjugate is also known to accumulate in tumor tissue and the lymphatic system through the EPR effect (enhanced permeability and retention). , SMA copolymers have also been shown to noncovalently bind with albumin during systemic circulation, thereby reducing polymer clearance from the body, and SMA has been conjugated with other anti-cancer agents to exploit this property .…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] The reactivity of maleic anhydride with hydroxyl and amine groups leads to a variety of modifications of PSMA. [10][11][12][13][14] For example, Pal et al [15] reported a long-chain monoalcohol esterified PSMA, consisting of PSMA esterified with n-decanol for a study of the environmental degradability of LLDPE. Lee et al reported the reaction of poly(ethylene glycol)400 (PEG400) with PSMA, and the study of the effect of lithium perchlorate (LiCIO 4 ) on the copolymer form and the interaction between Li + and PSMA-PEG.…”
Section: Introductionmentioning
confidence: 99%